1984
DOI: 10.1111/j.1532-5415.1984.tb05849.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe Symptomatic Hyponatremia in Elderly Outpatients: The Role of Thiazide Therapy and Stress

Abstract: Severe symptomatic hyponatremia (serum sodium level 112 +/- 5.5 mEq/l) was encountered in six elderly outpatients within four days of the onset of thiazide therapy. Associated polydipsia was present in two of these patients, but the thiazides alone appeared responsible in the others. In three other elderly outpatients, severe hyponatremia (serum sodium level 112 +/- 5.25 mEq/l) developed after the acute emotional stress of relocation from their place of abode to a nursing home or hospital. Recurrent episodes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Five of the patients on thiazides resemble those described by Fichman et al (1971), Husby & Marthedal (1981 and Booker (1984), in whom hyponatraemia occurred within a short time of thiazide administration. Rechallenge by a single dose ofhydrochlorothiazide again caused a large fall in serum sodium in some patients (Fichman et al, 1971), and in one of our patients who was thus re-challenged, there was a reduction of serum sodium of 16 mmol/l within 24 hours.…”
Section: Methodsmentioning
confidence: 60%
See 1 more Smart Citation
“…Five of the patients on thiazides resemble those described by Fichman et al (1971), Husby & Marthedal (1981 and Booker (1984), in whom hyponatraemia occurred within a short time of thiazide administration. Rechallenge by a single dose ofhydrochlorothiazide again caused a large fall in serum sodium in some patients (Fichman et al, 1971), and in one of our patients who was thus re-challenged, there was a reduction of serum sodium of 16 mmol/l within 24 hours.…”
Section: Methodsmentioning
confidence: 60%
“…A number of authors have suggested inappropriate ADH secretion as a cause for hyponatraemia induced by thiazides (Fichman et al, 1971;Horowitz et al, 1972;Luboshitzky et al, 1978;Husby & Marthedal, 1981;Booker, 1984). In the present investigation, fractional uric acid clearances were used to determine whether diuretic-induced hyponatraemia could be due to excess ADH activity or to other causes.…”
Section: Introductionmentioning
confidence: 90%
“…Although not structurally related to the catecholamines or cardiac glycosides, amrinone produces positive inotropic and vasodilatory effects, 1 increasing cardiac index and decreasing the pulmonary capillary wedge pressure without affecting arterial blood pressure or heart rate. 2 The mechanism of amrinone's positive inotropic activity, although not fully delineated, may be related to its ability to inhibit the phosphodiesterase III enzyme. 3 Amrinone is approved for intravenous administration.…”
Section: Extractomentioning
confidence: 99%
“…Since that time, numerous additional cases have been reported, and diuretics are now recognized to be one of the most important causes of severe hyponatremia [2,3]. Yet, despite several relevant studies, the mechanism and optimal treatment of diuretic-induced hyponatremia remain unclear.…”
Section: Introductionmentioning
confidence: 99%